Comprehensive Analytical Characterization of the Proposed Biosimilar Trastuzumab - Dakshinamurthy, Pravin Kumar; Gothandam, Kodiveri Muthukaliannan (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Biosimilars to monoclonal antibodies were developed to increase the accessibility of this drug and reduce the costs of this therapy without compromising on its quality, safety, and efficacy. The objective of this research is to describe the orthogonal analytical methods used for the physicochemical and biological characterization of the biosimilar proposed to trastuzumab, which is the basis of the biosimilar development program. Methods: The orthogonal analytical methods for characterization of the proposed biosimilar to trastuzumab were segregated based on the quality attributes of the product, such as the primary structure was evaluated using peptide mapping and high-end mass spectrometry, secondary and tertiary structure was evaluated using circular dichroism, fluorescence, and absorbance spectroscopy, identity and size heterogeneity were evaluated using Western blotting, size exclusion chromatography and capillary electrophoresis, charge heterogeneity, glycan heterogeneity and hydrophobic heterogeneity were evaluated using by weak cation exchange liquid chromatography, hydrophilic interaction chromatography and reverse phase liquid chromatography, antigen binding and Fc gamma receptor binding was evaluated using surface plasmon resonance, flow cytometry and cell-based enzyme linked immunosorbent assay, antiproliferation and antibody dependent cellular cytotoxicity were evaluated using in vitro cell-based bioassay. Results and Conclusion: The results of a comprehensive analytical characterization of the proposed biosimilar to the innovator trastuzumab confirm that the physicochemical and biological properties of the proposed biosimilar were comparable to those of the innovator molecule trastuzumab.
Keywords: Therapeutic Monoclonal Antibody; Biosimilar; Critical Quality Attributes; Charge Variants; Aggregates; Fragments; Post-translational modifications; N-Linked; Glycan and Antibody dependent cellular cytotoxicity